Anti-Aging Efficacy of Mangrove Leaf Extract Cream Assessed by SPF and Collagen Density Enhancement: In Vitro and In Vivo Approaches - Wardani, I Gusti Agung Ayu Kusuma; Adrianta, Ketut Agus; Udayani, Ni Nyoman Wahyu; Amaral, Meriana Barreto; Suena, Ni Made Dharma Shantini (Jurnal Ilmiah Medicamento, 2026)
Background: Excessive ultraviolet (UV) exposure is a major contributor to skin photoaging through oxidative stress, inflammation, and collagen degradation. Mangrove leaf extract (Xylocarpus granatum J. Koenig) contains bioactive compounds with potential photoprotective properties. In this study, the extract was formulated into an oil-in-water (O/W) cream suitable for cosmetic applications.Objective: This study aimed to determine the in vitro sun protection factor (SPF), percentage of erythema transmission (%Te), and percentage of pigmentation transmission (%Tp) of the mangrove leaf extract cream, and to evaluate its effectiveness on UVB-exposed guinea pig skin using collagen density as an anti-aging biomarker.Methods: In vitro assessments of SPF, %Te, and %Tp were performed using UV–Vis spectrophotometry. In vivo evaluation was conducted using 20 guinea pigs to examine the effect of the cream on collagen density through histopathological analysis of UVB-exposed skin.Results: The mangrove leaf extract cream exhibited strong photoprotective activity, with SPF values ranging from 20.68 ± 0.51 to 33.70 ± 0.67, %Te values from 3.13 ± 0.08 to 1.75 ± 0.03, and %Tp values from 4.40 ± 0.12 to 3.31 ± 0.03. Furthermore, the cream significantly increased collagen density (71.77 ± 5.27–81.02 ± 0.96) compared with the positive control (52.16 ± 2.32) (p < 0.05).Conclusions: The mangrove leaf extract cream provides effective protection against UVB radiation, characterized by high-protection SPF, extra-protection %Te, and sunblock-level %Tp. The 5% formulation significantly enhanced collagen density, supporting its potential as a natural anti-aging active ingredient for photoaging prevention through improved UV protection and dermal structure.